Study on causes of delay and cost overruns in heritage renovation of Bhaktapur - Sukamani, Umesh; Shrestha, Hari Mohan (Journal of Science and Engineering, 2018)
A fresh and present look at the performance and delivery of heritage projects is required because few studies have been conducted to explore the specific project management and participant issues that contributed failed elements (time and cost) in heritage projects. The major contribution of this research is in the guidance for improvement to help avoid delays and cost overruns in future heritage renovation projects. Bhaktapur municipality is rich in heritage; here the tourism market is one of the source of economy. Bhaktapur municipality has been selected for this study because many of the heritage renovation projects have been completed each year. Most of heritage renovations have been done with the help of users committee and amanat. Tourism has become an important economic factor for the region. So the heritage renovation is studied with the impact of the delay in the works. The research design for this study is more qualitative than quantitative. The main causes of delay have been found as difficulties in financing projects and poor managerial skills. Similarly, the causes of the cost overruns have been found as material cost increased due to inflation.